THE BATTLE OF MEMORIES: FRAMES OF MEDIA REPRESENTATION OF THE YUGOSLAVIAN PAST - Drašković, Brankica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
The aim of the paper was to establish the frames of remembering the Yugoslavian past in the Serbian media in the context of two important anniversaries which coincided: the centenary of the first Yugoslavia (the Kingdom of SHS) and the 75th anniversary of the second, socialist Yugoslavia. Drawing upon the theoretical and methodological paradigms of the memory culture and the concept of framing, the analysis was focused on the coverage of five daily newspapers online editions: Blic, Danas, Večernje novosti, Politika, Kurir and central news programs of the public broadcaster Radio Television of Serbia and Television N1 in the period between 28th November and 4th December. The results of the conducted research showed the presence of three frames: revisionist, nostalgic and critical counter-narrative, constructed by different strategies. The media framing of the Yugoslavian past reflects the decades-long frozen conflict of memory in public discourse between official, institutional, and unofficial critical, engaged, so-called, counter-memories.
Keywords: Serbia; Yugoslavia; nostalgia; frames; media; culture of memory; memory